Receptor binding mechanisms of Clostridioides difficile toxin B and implications for therapeutics development. (13th December 2021) - Chen, Peng; Jin, Rongsheng
Abstract : Clostridioides difficile is classified as an urgent antibiotic resistance threat by the Centers for Disease Control and Prevention (CDC). C . difficile infection (CDI) is mainly caused by the C. difficile exotoxin TcdB, which invades host cells via receptor‐mediated endocytosis. However, many natural variants of TcdB have been identified including some from the hypervirulent strains, which pose significant challenges for developing effective CDI therapies. Here, we review the recent research progress on the molecular mechanisms by which TcdB recognizes Frizzed proteins (FZDs) and chondroitin sulfate proteoglycan 4 (CSPG4) as two major host receptors. We suggest that the receptor‐binding sites and several previously identified neutralizing epitopes on TcdB are ideal targets for the development of broad‐spectrum inhibitors to protect against diverse TcdB variants. Abstract : FZD and CSPG4 are two major host receptors for TcdB, which could simultaneously bind to TcdB if they are expressed on the same cell surface. Moreover, the CSPG4‐binding site is highly conserved among most known TcdB variants. We suggest that the receptor‐binding sites and several previously identified neutralizing epitopes on TcdB are ideal targets for the development of broad‐spectrum inhibitors to protect against diverse TcdB variants.